Self-Control at Meals in Order Not to Gain Weight and Its Relationship with Food Cravings in Low-Carb Dieters - Jônatas Oliveira; Táki Athanássios Cordás (Obesities, 2021)
Aims: This study’s objective was to verify the level of food cravings and cognitive restraint in women who reported having followed a low-carb diet. Methods: The volunteers filled out the binge eating scale, the cognitive restraint subscale, the food cravings trait and state questionnaires, and the food frequency questionnaire. This study has also compared participants according to the self-reported practice of a low-carb diet. Parametric tests were used to compare the groups and Pearson’s correlations between some variables of interest (p > 0.05 adopted). Results: According to the question regarding the practice of the low-carb diet, 39 participants had tried a low-carb diet in the last six months (46.2% of these with binge eating) and 48 did not (16.7% with binge eating). Dieters showed higher levels of binge eating, cognitive restriction, and food cravings (trait and state). Dieters consumed less rice and bread but did not present lower consumption of sweets. Correlations showed that for dieters who ‘Consciously hold back at meals in order not to gain weight’, it was negatively associated with ‘Intention and plans to eat’, ‘positive reinforcement’ and ‘relieving negative states’ and food cravings scores. Conclusions: Despite the higher levels of cognitive restriction in dieters, they are negatively correlated with food craving factors and negatively associated with the consumption of sweets.